ANALISIS PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Ericke Fridatien (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to examine capital structure, profitability and dividend policy on firm value. This study used a sample of mining companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This sampling method is using purposive sampling. Based on predetermined criteria, a sample of 17 companies was obtained. This research was conducted with a period of 3 years, bringing the total sample to 51 companies. The type of data used is secondary data taken from the company's financial statements. The analysis technique used in this study is multiple linear regression using the SPSS 26 application program. The results show that capital structure (DER) has no effect on firm value (PBV), while profitability (ROA) has a significant positive effect on firm value (PBV). And dividend policy (DPR) has a significant positive effect on firm value (PBV).